Global trends and hotspots evolution in soil microplastic pollution research: A bibliometric analysis based on the Web of Science - Bogui Pan; Fengtao Zhang; Xiaoqiong Zhu; Li Huang; Yang Wu; Jing-Qian Tang; Nai-Xian Feng (Ecological Indicators, 2024)
Soil microplastic (MP) pollution is a growing global environmental issue leading to a series of ecosystem problems and functional losses. However, understanding the advances and trends in soil MP pollution research proved to be difficult based on individual studies. Herein, CiteSpace visualization analysis software was used to sort the literature obtained on soil MP research from the Web of Science (WoS) TM core collection database, and bibliometric analysis of publication volume, country/region, keywords and other information was conducted. Results showed that soil microplastics (MP) research had much lower publication volume than hydrological system MP research, and was still in its developing stage. However, the number of research hotspots in soil MP research increased continuously since 2018. Countries such as China, the United States, the Netherlands and Australia have published more papers in this field than other countries, and collaboration among research institutions is strong. The source, pollution status, analysis methods and toxic effects of MPs in soils are current research hotspots. In the future, the focus of MP research in terrestrial ecosystems should shift from ecotoxicology to the impact of MPs on ecosystems and earth system feedback. The bibliometric analysis results of this study can serve as a reference for in-depth studies of the pollution status of MPs in soils. For MP soil pollution research, cross-background, cross-institution, cross-country cooperation and cross-disciplinary roles should be encouraged to accelerate the growth and diversification of the field.